Utilization of Fauna for Therapeutic Purposes by the Newar Community in Bhanu Municipality, Tanahun, Nepal - Shrestha, Nishana; Bajracharya, Sony (Amrit Research Journal, 2023)
The project has interviewed 70 people of Newar community including 37 females and 33 males of different age groups and occupations. Due to major profession of people with farming and animal husbandry, it has provided beneficial knowledge on ethnomedicinal practices to cure different ailment problems like gastritis, asthma, dysentery, cold, cough, back pain, crack heels, anxiety, menstrual cycle problem, burnings, eye cyst etc. 35 species of faunas are used for 9 different ailment categories. Out of 35 fauna species, 29 were vertebrates (15 Mammals, 11 Aves, 2 Pisces and 1 Reptile) and 6 were invertebrates (Order: Hymenoptera, Neuroptera, Stylommatophora and Decapoda). Apis sp. (0.1) and Bos taurus (0.9) has the highest Use Value; Gallus gallus domesticus, Bubalus bubalis, Ovis aries, Columba sp. has 100% Fidelity Level. There was no significant correlation between the fidelity level in ailment categories and animal use value (p<0.05) indicating that the animals frequently used for a particular ailment category of local people are not necessarily those used commonly in the study area. Newar community considered animal and their products have tremendous zootherapeutic potential in curing heath related problems. This project aims to pass the therapeutic uses of faunas to the new generation that barely are aware about side effects and free practices followed by their ancestors.